Pengembangan Aplikasi Telegram Untuk Memperoleh Informasi Saham di Bursa Efek Indonesia - Lucky Kartanto (CV. Multi Kreasi Media, 2023)
In the era of the fourth industrial revolution, the stock market has become the main focus of all countries as it plays an important role in the economic development of a country. Some countries have proven that the stock market can be a trigger for their economic progress, so the more the stock market develops, the greater the possibility for a country's economic progress. In the field of finance, particularly in stock investment analysis, computer and information technology is essential. High computational power enables investors to perform complex analysis using historical stock data in large quantities. One way to obtain stock data is by using the Telegram application which has a Telegram bot. Keywords: Industry 4.0 revolution, Information technology, Telegram bot.